THE EFFECT OF TOUCH THERAPY ON BODY TEMPERATURE IN NEWBORNS IN THE SELE BE SOLU HOSPITAL, SORONG CITY, PAPUA, INDONESIA - Pongoh, Ariani (Public Health of Indonesia, 2019)
Background: Newborns are not able to regulate their body temperature directly and are quickly getting cold. If heat loss is not immediately prevented, the baby will experience hypothermia and is at risk of falling ill leading to death. Hypothermia is a decrease in body temperature below 36.50C. One way to handle it is by giving touch therapy.Objective:  This study aims to analyze the effectiveness of touch therapy to stabilize baby temperature in newborns in Sele Be Solu Hospital in Sorong City, Papua Indonesia.Methods: The study used a quasi-experimental design with pretest and posttest control group design. There were 32 patients, which 16 patients were assigned in the intervention group and the control group. Data were analyzed using Independent t-test.Results: The results showed that there was a significant increase in the body temperature of newborns in the intervention group (p=.000).Conclusion:  Touch therapy is effective for increasing body temperature in the newborns.